DEPRESSION SYMPTOM AND NUTRITIONAL STATUS OF ELDERLY IN JEMBER REGENCY - Ninna Rohmawati (Fakultas Kedokteran Universitas Lampung, 2014)
Background: Indonesia is one of countries which have inhabitant of elderly highest ever. In 2020 Indonesia will be the fifth highest of elderly. East Java province has included in groups the area having structure aging population. East Java have the number of elderly second highest after Yogjakarta (10.4%). The growing number of elderly would have become complex problem for senior family and community including the physical aspects, biological, mental, or socially economy. Along with the matter will affect on nutrition status for elderly. The aim of this studi is to determine correlation between depression symptom with nutritional status of elderly in Jember regency. Method: This research was observational with cross sectional design. Subjects were elderly in Sumbersari sub-district, Jember regency who fulfilled inclusion criteria. Research subjects consisted of 120 elderly. Depression symptom was measured with Geriatric Depression Scale-15 (GDS-15), dietary intake with semi quantitative food frequency questionnaire (SQFFQ) method, and nutritional status was determined based on body mass armspan (BMA). Data were analyzed with chi squaretest and multiple logistic regression. Result: The proportion of depression symptom in Sumbersari sub-district, Jember egency was by 27,5%. Most of the subjects who suffer depression symptom have more and less nutritional status 69,7% (23 elderly), and have a good nutritional status for as many as 10 elderly (30.3%). The greatest distribution of subjects with depression as much as 31 elderly (33.7%) and the subject with no depression as many as 61 elderly (66.3%) female subjects in the group scattered. Conclusion: Significant correlation was found between depression symptomand nutritional status (p=0.027). [JuKe Unila 2014; 4(8):185-193]